Automated Calibration of Farm-Sale Mixed Linear Programming Models using Bi-Level Programming - Wolfgang Britz (German Journal of Agricultural Economics (GJAE), 2021)
We calibrate Linear and Mixed Integer Programs with a bi-level estimator, minimizing under First-order-conditions (FOC) conditions a penalty function considering the calibration fit and deviations from given parameters. To deal with non-convexity, a heuristic generates restart points from current best-fit parameters and their means. Monte-Carlo analysis assesses the approach by drawing parameters for a model optimizing acreages under maximal crop shares, a land balance and annual plus intra-annual labour constraints; a variant comprises integer based investments. Resulting optimal solutions perturbed by white noise provide calibration targets. The approach recovers the true parameters and thus allows for systematic and automated calibration.
Keywords: 330; linear programming; mixed linear programming; calibration; bi-level programming; farm-scale model